Common Fixed Point Theorems For Weakly Compatible Mappings In Symmetric Spaces - GOYAL, A.K. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this paper some common fixed point theorem has been established by using weakly compatible mappings and E.A property which improves and extends similar known results in the literature. Key words: Symmetric spaces, common fixed points, weakly compatible mappings. 2010 AMS SUBJECT CLASSIFICATION CODE : 54H25, 47H10